Feasibility Study on the Implementation of Clinic SIM and ERM integrated Pcare as a BPJS Kesehatan Application at Udayana University Clinic - luh sudiarmini; Fajar Manuaba Ida Bagus; Hariyasa Sanjaya I Nyoman (WMJ (Warmadewa Medical Journal), 2020)
The development of an information system and communication technology has an impact on the health service sector in the form of electronic-health or e-health. One of the e-health applications is a Clinic SIM and electronic medical records. Not only provides information for the academic communities, but Udayana University Clinic also serves BPJS Kesehatan patients since 2014. After occupying a new building, there have been various obstacles related to the implementation of the management information system. Which it is still being done manually and limited space to store medical record files. One of the efforts to overcome this problem is by implementing a Clinic SIM and ERM. Before the implementation of these activities, a feasibility study was proposed on the application of CSIM and ERM integrated BPJS Healthcare. The purpose of this study was to determine the feasibility of implementing Clinic SIM and ERM which are integrated with Pcare-BPJS at Udayana University Clinic. This study used a qualitative research design. Data collection was started between December 2019 and January 2020 using the in-depth interview method on 9 informants. This study informs that the application of Clinic SIM and ERM integrated BPJS Kesehatan meets the feasibility aspect based on acceptance, demand, integration, and practicality. Conclusion: the obstacles in this study are related to the implementation aspect due to lack of human resources, infrastructure, implementation methods, budget, and minimal application of Clinic SIM and ERM. Keywords: feasibility study, Clinic SIM, ERM, Pcare BPJS Kesehatan